Osmoregulated Periplasmic Glucans Transmit External Signals Through Rcs Phosphorelay Pathway in Yersinia enterocolitica - Meng, Jiao; Huang, Can; Huang, Xiaoning; Liu, Dingyu; Han, Beizhong; Chen, Jingyu (Frontiers in Microbiology, 2020)
Fast response to environmental changes plays a key role in the transmission and pathogenesis of Yersinia enterocolitica. Osmoregulated periplasmic glucans (OPGs) are known to be involved in environmental perception of several Enterobacteriaceae pathogens; however, the biological function of OPGs in Y. enterocolitica is still unclear. In this study, we investigated the role of OPGs in Y. enterocolitica by deleting the opgGH operon encoding enzymes responsible for OPGs biosynthesis. Complete loss of OPGs in the ΔopgGH mutant resulted in decreased motility, c-di-GMP production, biofilm formation and smaller cell size, whereas the overproduction of OPGs through restoration of opgGH expression promoted c-di-GMP/biofilm production and increased antibiotic resistance of Y. enterocolitica. Gene expression analysis revealed that opgGH deletion reduced transcription of flhDC, ftsAZ, hmsT and hmsHFRS genes regulated by the Rcs phosphorelay system, whereas additional deletion of rcs family genes (rcsF, rcsC or rcsB) reversed this effect and restored motility and c-di-GMP/biofilm production but further reduced cell size. Furthermore, disruption of the Rcs phosphorelay increased the motility and promoted the induction of biofilm and c-di-GMP production regulated by OPGs through upregulating the expression of flhDC, hmsHFRS and hmsT. However, deletion of genes encoding the EnvZ/OmpR phosphorelay downregulated the flhDC, hmsHFRS and hmsT expression, leading to the decreased motility and prevented the induction of biofilm and c-di-GMP production regulated by OPGs. These results indicated that Rcs phosphorelay had the effect on OPGs-mediated functional responses in Y. enterocolitica. Our findings disclose part of the biological role of OPGs and the underlying molecular mechanisms associated with Rcs system in the regulation of the pathogenic phenotype in Y. enterocolitica.